The picture chart and its metaphorical implications in the prose, Opera and theater Text of Mohammed Ali Al-Khafaji. Research withdrawn from Thesis (Journal of the College of Basic Education, 2022)
Gracious is our Allah and peace upon Allah's Messenger and his family and his Colleagues. The current study focuses on studying the pictures chart in the prose and Opera plays of " Mohammed Ali Al-Khafaji "; this experience with all its human presence ، has been needed for creative imagination and its indicative depth and its strength for bringing about human and artistic effects as that being reflected on the pictures chart.